Ergothioneine levels in an elderly population decrease with age and incidence of cognitive decline; a risk factor for neurodegeneration? - Cheah, Irwin K.; Feng, Lei; Tang, Richard M.Y.; Lim, Keith H.C.; Halliwell, Barry (Biochemical and biophysical research communications, 2016)
Ergothioneine (ET), a naturally occurring thione, can accumulate in the human body at high concentrations from diet. Following absorption via a specific transporter, OCTN1, ET may accumulate preferentially in tissues predisposed to higher levels of oxidative stress and inflammation. Given its potential cytoprotective effects, we examined how ET levels change with age. We found that whole blood ET levels in elderly individuals decline significantly beyond 60 years of age. Additionally, a subset of these subjects with mild cognitive impairment had significantly lower plasma ET levels compared with age-matched subjects. This decline suggests that deficiency in ET may be a risk factor, predisposing individuals to neurodegenerative diseases. [Display omitted] •Blood levels of ergothioneine in elderly were found to decline with age.•Blood ergothioneine significantly declines with incidence of early dementia.•Decline not due to change in diet or expression of ergothioneine transporter.•Declining blood ergothioneine suggested to be a risk factor for neurodegeneration.